Advisory, Collaborative and Scrutinizing Roles of Deliberative Mini-Publics - Setälä, Maija (Frontiers in Political Science, 2021)
The normative point of departure in this article is that mini-publics can “complement” representative democracy only if they enhance inclusive processes of mutual justification among elected representatives who are responsible for public decisions. This article distinguishes three different roles of mini-publics in representative decision-making. Mini-publics can be 1) advisory when they provide input for collective will-formation in the representative arena, 2) collaborative when they involve elected representatives in the deliberative process, 3) scrutinizing when they check representative decision-making. The article analyzes strengths and weaknesses of these roles of mini-publics. Advisory mini-publics are particularly vulnerable to “cherry-picking.” While collaborative uses of mini-publics may facilitate inclusive reason-giving among elected representatives, they entail risks of representative dominance. Scrutinizing use of mini-publics seem particularly promising from the normative perspective, but it requires a well-defined institutional framework. The article concludes that while there are ways to avoid problems emerging in these different roles, political context is crucial in terms of the deliberative impact of mini-publics.